Exploring the Learning Experience of High-Performing Preclinical Undergraduate Dental Students: A Qualitative Study - Galvin Sim Siang Lin; Wen Wu Tan; Kelvin I. Afrashtehfar (MDPI AG, 2022)
The current study aimed to explore the perceptions of high-performing undergraduate dental students in learning dental materials science. One-on-one semi-structured interviews with high-performing students who scored 80 marks and above in dental materials were conducted using an online video-chat platform. A purposeful sampling method was employed, and six students fulfilled the criteria. The interviews were audio-recorded, transcribed verbatim, and analyzed qualitatively using a thematic approach. Three major themes were identified: (1) Learning strategies, (2) Learning enablers and barriers, and (3) Coping with learning challenges. Six sub-themes emerged from the "learning strategies" theme: memorizing and repeating, peer learning, seeking learning resources, study planning, paying attention during class, and mnemonics. The enabler sub-themes include motivation, lecture notes, teachers, and hands-on, whereas the barrier sub-theme is content understanding. Moreover, family support and de-stress appeared as the sub-themes in coping with learning challenges. In short, the present exploratory study identified several major themes and sub-themes that can help dental educators comprehend the complexity of learning dental materials science and how it affects students' academic performances. The current findings also offer learning recommendations for low-performing students to improve their academic achievements in the dental materials science course.